Оскисько тыныд: кылбуръёс / А. Д. Вотяков - Вотяков Александр Дмитриевич (Удмуртия, 1977)
Экземпляры: АБ (20140430) / Инвентарный номер: 61432 / Сис.шифр: С(Удм) / Авт.знак: В-79 / ГРНТИ: 17.82.10 / ББК: С(Удм)